Pengaruh Dosis Sludge dan Pupuk MKP Terhadap Pertumbuhan dan Hasil Tanaman Lobak Pada Tanah Gambut - Seli Seli; Basuni Basuni; Muhammad Pramulya (Perkebunan dan Lahan Tropika, 2021)
Effect of Sludge and MKP Fertilizer Doses on Radish Plant Growth and Yield on Peatsoils. The development of the horseraean plant in peat land is faced with the number of obstacles in low, low ph, inlet, high c-organics with varying degrees of maturity and low - base base soils that are causing the growth and development of plants to be stunted, That would make a sludge delivery out of MKP fertilizer. The study is aimed at seeing the effect that doses of sludge given and MKP fertilizers have on the growth and growth of turnip plants in the peat soil. The research was conducted on KEP’S Agroland at Jl. Sui Raya Dalam, Pontianak City from March 12th to April 31th  2021. The study uses field experimental methods with comprehensive design prosecutions consisting of 2 treatment factors. The first factor is the sludge with the levels of treatment and the second factor is MKP fertilizer. Each factor is repeated 3 times, each denteronomy consisting of 4 plant samples, making the total number of plants 108. The first factor is the dose of sludge and the second is the dose of MKP fertilizer which has three levels of treatment each. Every treatment is repeated three times. A sludge dose consists of 0, 200, 320 g/polybag (equivalent to 0, 25, 40 tons /ha), while the MKP dosage consists of 0, 2, 4 g/polybag (equivalent to 0, 150, 250 kg/ha). The observed variabel is that of the number of leaves, the fresh weight of the plant, the fresh weight of the bulbous, the length of the tuber diameter and the plant’s dry weight. The research suggests and that there is no interaction between her and MKP for all variables. The treatment of sludge and MKP involving a dose of sludge 25 tons/hectares is equivalent to 200 g/polybag and MKP 150 kg/hectares is equivalent to 2 g/polybag is an efficient gift.